ALIMENTARY-DEPENDENT RISK FACTORS OF ARTERIAL HYPERTENSION - S. Yu. Baglushkina (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The aim of the study was to carry out the analysis of food rations in order to study provision of patients with arterial hypertension with basic macronutrients. Analysis of nutrition condition was carried out by using the computer program. «The Analysis of the person's condition» (version 1.2, Scientific Research. Institute of Nutrition RAMS, 2003—2005), based, on the frequency of food substances consumption. The analysis of basic macronutrients showed that the content of proteins is below physiological norm on the whole, the content of carbohydrates and. fats was considerably higher than the physiological norm.. The results of the analysis of nutrition condition of patients with arterial hypertension, revealed, disorder of balanced, ration principles that require correction of a ration.